The effect of ginkgo biloba extract in experimental strangulation ileus in a rat model - Adnan ŞAHİN,; Ömer ÇOLAK,; Özkan ALATAŞ,; Cengiz BAYÇU,; H. Ahmet KASAP,; Bekir YAŞAR,; Ertuğrul KARAHÜSEYİNOĞLU,; Haluk KİPER, (Turkish Journal of Gastroenterology, 2020)
-